Revisiting DARPP-32 in postmortem human brain: changes in schizophrenia and bipolar disorder and genetic associations with t-DARPP-32 expression - Kunii, Y; Hyde, T M; Ye, T; Li, C; Kolachana, B; Dickinson, D; Weinberger, D R; Kleinman, J E; Lipska, B K (Molecular psychiatry, 2014)
Dopamine- and cAMP-regulated phosphoprotein of molecular weight 32 kDa (DARPP-32 or PPP1R1B ) has been of interest in schizophrenia owing to its critical function in integrating dopaminergic and glutaminergic signaling. In a previous study, we identified single-nucleotide polymorphisms (SNPs) and a frequent haplotype associated with cognitive and imaging phenotypes that have been linked with schizophrenia, as well as with expression of prefrontal cortical DARPP-32 messenger RNA (mRNA) in a relatively small sample of postmortem brains. In this study, we examined the association of expression of two major DARPP-32 transcripts, full-length (FL-DARPP-32) and truncated (t-DARPP-32), with genetic variants of DARPP-32 in three brain regions receiving dopaminergic input and implicated in schizophrenia (the dorsolateral prefrontal cortex (DLPFC), hippocampus and caudate) in a much larger set of postmortem samples from patients with schizophrenia, bipolar disorder, major depression and normal controls (>700 subjects). We found that the expression of t-DARPP-32 was increased in the DLPFC of patients with schizophrenia and bipolar disorder, and was strongly associated with genotypes at SNPs (rs879606, rs90974 and rs3764352), as well as the previously identified 7-SNP haplotype related to cognitive functioning. The genetic variants that predicted worse cognitive performance were associated with higher t-DARPP-32 expression. Our results suggest that variation in PPP1R1B affects the abundance of the splice variant t-DARPP-32 mRNA and may reflect potential molecular mechanisms implicated in schizophrenia and affective disorders.